Neem (Azadirachta indica): towards the ideal insecticide - Benelli, Giovanni; Canale, Angelo; Toniolo, Chiara; Higuchi, Akon; Murugan, Kadarkarai; Pavela, Roman; Nicoletti, Marcello (Natural product research, 2017)
Pesticide resistance is going to change rapidly our antibiotics and insecticides arsenal. In this scenario, plant-derived natural products are considered valuable candidates to reverse this negative trend. Growing research attention is focused on neem (Azadirachta indica, Meliaceae), exploring the utility of its products as insecticides and antibiotics. In this review, we summarised the knowledge on neem oil and neem cake by-products in arthropod pest control, with special reference to mosquito vectors of public health importance. To the best of our knowledge, neem-borne products currently showed effective and eco-friendly features, including little non-target effects, multiple mechanisms of action, low cost, easy production in countries with limited industrial facilities. In particular, the potentiality of neem cake as ideal and affordable source of mosquitocidal compounds in anopheline and aedine control programmes is outlined. Overall, we propose the employ of neem-based products as an advantageous alternative to build newer and safer arthropod control tools.
Keywords: etnobotanika; Animals; Azadirachta; Insecticides; glyceridy; zvířata; Terpenes; Pest Control; Ethnobotany; kontrola škůdců; insekticidy; Glycerides; terpeny